Phase stability and thermodynamic database validation in a set of non-equiatomic Al-Co-Cr-Fe-Nb-Ni high-entropy alloys. (January 2019) - Detrois, Martin; Antonov, Stoichko; Tin, Sammy
Abstract: A series of six high-entropy alloys in non-equiatomic proportions were produced to study the phase stability across a range of compositions within the Al-Co-Cr-Fe-Nb-Ni system. Phase identification was performed using SEM, TEM, and XRD and computational tools were employed for comparison to the experimental findings. Complex microstructures were obtained following exposure at 900 °C with precipitation of Laves, NiAl, γ′ and δ phases. Primary and secondary Laves populations were identified and found to become more stable with increasing Fe and Nb content. Additions of Nb promoted the formation of thin, plate-like, δ phase at the expense of the secondary Laves. The NiAl phase was observed to precipitate in the alloys with high Fe content, above the γ′ solvus temperature. Overall, the thermodynamic predictions using Thermo-Calc with the TCNi8 database were accurate with respect to identifying the phase composition, while TTNi8 provided good phase stability results. However, significant differences were observed with respect to the solvus temperatures of the precipitate phases. Graphical abstract: Highlights: Phase formation in the non-equiatomic Al-Co-Cr-Fe-Nb-Ni system was explored. The low enthalpy of mixing of Nb led to the formation of secondary phases. Nb is a potent γʹ stabilizer, showing a synergistic effect with Al. Excessive additions of Nb and Fe promote the formation of Laves and NiAl phases. CALPHAD predictions are reliable depending on the database and properties measured.